Effects of ice slurry ingestion on 5km run time and thermoregulatory responses - Lee, Leroi Rong Zu (Nanyang Technological University, 2022)
Ice slurry (IS) ingestion is used as a cooling strategy to not only reduce heat injury risk, but also to enhance endurance exercise performance by lowering heart rate (HR) and body temperature (BT) during exercise. However, studies have yielded inconclusive results with respect to its ergogenic and thermoregulatory properties. Therefore, the purpose of this research was to examine the effects of pre-exercise IS versus chilled placebo drink (P) ingestion on 5km run time and thermoregulatory responses. It was hypothesised that there would be no significant differences between the conditions. Over two days, 14 physically active males (Age: 23.79 ± 1.81; Mass: 70.71 ± 4.66 kg; Height: 1.74 ± 0.04 m; BMI: 23.27 ± 1.53 kg/m2) ingested 7.5 ml/kg body weight of either an IS (-1°C) or a P (4°C), in a randomised order, before performing an all-out 5km run. Their run time (RT), HR, BT, and perceived exertion (PE) were recorded and analysed. Nine participants ran faster after ingesting IS and mean RT was 1.2% faster in the IS condition (p = 0.113). No significant differences (p > 0.05) were observed for the other parameters. Additionally, four and six participants experienced gastrointestinal discomfort and sphenopalatine ganglioneuralgia, respectively, from the ingestion of IS. In conclusion, the pre-exercise ingestion of IS and cold fluids have similar ergogenic and thermoregulatory effects over an all-out 5km run. However, given that IS ingestion increases the occurrences of gastrointestinal issues and sphenopalatine ganglioneuralgia, ingesting cold fluids may be a more preferable pre-exercise cooling strategy for athletes.